Laboratory evaluation and transfusion support of patients with autoimmune hemolytic anemia - Reardon, John E; Marques, Marisa B (American journal of clinical pathology, 2006)
Although some autoantibodies do not cause hemolysis and their workup is performed routinely, others might lead to life-threatening hemolysis. In the latter situation, the pathologist often is involved in the urgent decision to transfuse before completion of the evaluation. However, every effort must be made to exclude the presence of concurrent alloantibodies. This identification of RBC autoantibodies is less common than alloantibody identification, and the evaluation often requires techniques and expertise available only in specialized laboratories. Unlike emergency release of units for trauma victims, an autoantibody by definition will react with all units in the inventory; thus, all crossmatches are expected to be incompatible. To avoid additional untoward consequences of transfusion, there has to be close communication between the consulting pathologist and the clinician, including close monitoring of the patient during and after transfusion. This review is intended to serve as a guide to general pathologists in the appropriate evaluation and interpretation of laboratory tests in the diagnosis and management of autoimmune hemolytic anemia.